Estrategias didácticas constructivistas para la potenciación del rendimiento académico de los estudiantes en Biología. Año lectivo 2022-2023 - Hidalgo Lojan, Patricia Betsabeth (2023)
The constructivist didactic strategies are essential to strengthen the teaching and learning process, because they provide a highly interactive environment for students, facilitating the classroom process. This research had as a goal: To enhance the academic performance of students through the application of constructivist didactic strategies that strengthen the teaching and learning process in Biology subject of first year of Baccalaureate in Beatriz Cueva de Ayora High school. Academic year 2022 – 2023. The inductive method was used for the research, with a qualitative approach, on the other hand, and taking into account the temporality, the research is transversal, since the diagnosis through the achieve of final results correspond to a relatively short period of time, moreover, regarding the nature o the information, it is a participative action research (PAR), thus, during the proposal implementation, students´ participation, and teachers´ interaction was encouraged. The achieved results through the evaluation instruments, show that constructivist didactic strategies offer great possibilities to improve the educative practice, and the majority of students coincide in that the collaborative work, gamification and case study, were the strategies with which they managed to better understand the topics developed in class. Thus, it was concluded that the application of constructivist didactic strategies strengthens the teaching and learning process of Biology, enhancing the improvement of the academic performance of students of first year of baccalaureate of “Beatriz Cueva de Ayora” High school, academic year 2022- 2023. Keywords: Intervention proposal, classroom process, Didactic material, Teaching and Learning.